An experimental and theoretical study of the valence shell photoelectron spectrum of bromochlorofluoromethane - Holland, David M.P.; Potts, A. W.; Karlsson, L.; Novak, I.; Zaytseva, I. L.; Trofimov, A. B.; Gromov, Evgeniy; Schirmer, Jochen (Journal of physics. B, Atomic, molecular and optical physics, 2010)
The complete valence shell photoelectron spectrum of bromochlorofluoromethane (CHFClBr), covering the binding energy range ∼10-50 eV, has been recorded using synchrotron radiation and the observed structure has been interpreted using ionization energies and relative spectral intensities computed using the third-order algebraic-diagrammatic-construction (ADC(3)) scheme for the one-particle Green's function and the outer valence Green's function (OVGF) method. The theoretical results demonstrate that the inner valence region of the photoelectron spectrum is dominated by satellite structure. Angle-resolved photoelectron spectra, recorded at selected excitation energies, have enabled the orbital assignments for the outer valence bands to be confirmed. The four outermost photoelectron bands, ascribed to the two pairs of orbitals associated with the nominally chlorine and bromine lone-pairs, exhibit characteristic angular distributions. The photon energy dependent variations in the relative photoelectron band intensities provide additional support for the orbital assignments.
Gesehen am 15.03.2023